2017
DOI: 10.1111/ijfs.13589
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol composition and antioxidant capacity in pulp and peel of apricot fruits of various varieties and maturity stages at harvest

Abstract: Summary Polyphenol composition and antioxidant capacities of peel and pulp tissues of six apricot varieties were determined. Variations in polyphenol and antioxidant capacity based on variety (early‐maturing varieties and late‐maturing varieties) and harvest maturity (green mature and full mature) were assessed. The results of principal component analysis revealed that (+)‐catechin made the most important contributions to the antioxidant capacities of the pulp. As the (+)‐catechin content in ‘Dajie’ apricot de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 31 publications
7
40
0
Order By: Relevance
“…At the beginning of the shelf, the control fruit had the least browning and the CS‐50d was the largest. The browning degree of pear fruit gradually increased during the shelf life at room temperature, which is consistent with the results of apricot, longan, and peach (Fan, Jiao, Wang, Cao, & Jiang, ; Zhang & Quantick, ; Zhao et al, ). In comparison, the browning degree of CS‐50d fruit was significantly higher than that of other groups during shelf life.…”
Section: Resultssupporting
confidence: 88%
“…At the beginning of the shelf, the control fruit had the least browning and the CS‐50d was the largest. The browning degree of pear fruit gradually increased during the shelf life at room temperature, which is consistent with the results of apricot, longan, and peach (Fan, Jiao, Wang, Cao, & Jiang, ; Zhang & Quantick, ; Zhao et al, ). In comparison, the browning degree of CS‐50d fruit was significantly higher than that of other groups during shelf life.…”
Section: Resultssupporting
confidence: 88%
“…Our study showed a similar result and further found that the higher the level of bioactive compounds retained in “Xingmei” apricots, the less chilling injury occurred after long‐term storage at NFT, which may be due to the positive correlation between phenolics and antioxidant capacity (Liu et al, , ). These bioactive compounds, including phenolics, carotenoid, and ascorbic acid, have been shown to be the important active substances in the reactive oxygen scavenging system (Fan, Jiao, Wang, Cao, & Jiang, ).…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the ascorbic acid content of fruits, the analyte was extracted from 2 g fresh samples using Liu, Cao, and Jiang's method (), and the concentration of ascorbic acid was determined using high‐performance liquid chromatography (Liu et al, ). To investigate the phenolics and flavonoids content, samples were extracted from 10.0 g frozen apricot flesh as previous conditions (Fan, Jiao, Wang, Cao, & Jiang, ). Total phenolics (TPs) content and total flavonoids (TFs) content measurements were modified from Fan et al ().…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the phenolics and flavonoids content, samples were extracted from 10.0 g frozen apricot flesh as previous conditions (Fan, Jiao, Wang, Cao, & Jiang, ). Total phenolics (TPs) content and total flavonoids (TFs) content measurements were modified from Fan et al (). The carotenoids were extracted and measured following the method by Barba, Hurtado, Mata, and Ruiz ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation